(untitled) (Journal of Mathematical Study, 2015)
We study the existence of global strong solution to an initial-boundary value (or initial value) problem for the 3D nonhomogeneous incompressible Navier-Stokes equations. In this study, the initial density is suitably small (or the viscosity coefficient suitably large) and the initial vacuum is allowed. Results show that the unique solution of the Navier-Stokes equations can be found.